Periapical tissue reactions to calcium hydroxide and MTA after external root resorption as a sequela of delayed tooth replantation - Marao, Heloisa Fonseca [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Sonoda, Celso Koogi [UNESP]; Poi, Wilson Roberto [UNESP]; Esteves, Jonatas Caldeira [UNESP]; Santos Silva, Pedro Ivo [UNESP] (Wiley-Blackwell, 2012)
Clinical experience has shown that most avulsed teeth are replanted after a long extra-alveolar time and dry or inadequate wet storage, causing necrosis of periodontal ligament cells. This condition invariably leads to development of external root resorption, leaving the filling material in contact with the periapical connective tissues. In this study, the periapical tissue reactions to calcium hydroxide (CH) and mineral trioxide aggregate (MTA) were evaluated after occurrence of external root resorption as an expected sequela of delayed tooth replantation. Twenty male Wistar rats (Rattus norvegicus, albinus) had their right upper incisor extracted and maintained in dry storage for 60 min. Then, the dental papilla, enamel organ, pulp tissue, and periodontal ligament were removed, and the teeth were immersed in a 2% acidulated phosphate sodium fluoride solution, pH 5.5, for 10 min. The teeth were randomly assigned into two groups (n = 10), in which the canals were filled with either a CH and saline paste (CH group) or MTA (MTA group). The sockets were irrigated with saline, and the teeth were replanted. After 80 days, it was possible to observe large areas of replacement root resorption and some areas of inflammatory root resorption in both groups. More severe inflammatory tissue reaction was observed in contact with calcium hydroxide compared with the mineral trioxide aggregate. New bone formation was more intense at the bottom of the socket in the MTA group. In conclusion, as far as periapical tissue compatibility is concerned, intracanal MTA can be considered as a viable option for root canal filling in delayed tooth replantation, in which external root resorption is an expected sequela.